The Application of Psychological Induction in Public English Teaching of Physical Education in Universities - Wei Zhu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Objective: In order to study the application of psychological induction in public English teaching of physical education in universities, this study focuses students in sports schools. Methods: This is a related study on the problems and countermeasures in the current situation of English learning among students in sports colleges. The factors that affect the success or failure of learning are multifaceted, with students being the primary factor. Student factors include both intellectual and non-intellectual factors. The former is more complex because college English is a public compulsory course with a large number of students, and there is a significant intellectual gap in learning foreign languages. Despite this, we still need to teach students according to their aptitude as much as possible, divide them into different learning groups or levels through scientific intelligence tests and assessments, and organize targeted teaching, rather than adopting a unified teaching model. The survey on the current situation of public English learning among students in sports colleges mainly involves non-intellectual factors of students, including learning environment, conditions, foundation, motivation, needs, concepts, attitudes, habits, strategies, difficulties, and goals. From the principles of education, we should fully consider the factors of students themselves, who are the recipients of teaching behavior or activities. At the same time, we should also consider the factors of schools and teachers, such as the requirements for students, the standards set, and whether the courses and conditions provided to students meet the needs of market talents and students. To solve these problems that arise during the learning process, efforts from all aspects, especially the participation of English teachers, are needed. Results: There are many problems in the public English learning of sports college students, mainly reflected in their lack of interest in English learning and their intrinsic motivation as the main driving force; Through the analysis of the selection of learning content, application of learning methods, arrangement of extracurricular life, understanding of teaching plans, and establishment of learning plans, it is reflected that students in sports colleges have weak self-directed learning ability, low self-control ability, insufficient learning consciousness, poor learning content, relatively single learning strategies, insufficient diversity of learning paths, and relatively passive learning attitudes; The classroom atmosphere is relatively dull, with most students having poor initiative and persistence in learning English, and rarely reflecting on their own learning situation; The learning effect is not ideal, and the improvement in English practical application ability is not significant. There are also varying degrees of problems in English teaching materials, teaching methods, teaching methods, and teaching evaluation. Based on the current situation of teaching and learning public English courses in sports colleges, strategies and suggestions have been proposed to revise and improve the teaching syllabus, adjust English teaching content, improve English teaching methods, improve the English teaching system, and implement graded teaching to solve the problems. Conclusion: It aims to provide reference opinions for the majority of Physical Education vocational English teachers on how to improve students' interest in English learning.